2015
DOI: 10.1021/jp510995z
|View full text |Cite
|
Sign up to set email alerts
|

Initial Mechanisms for the Decomposition of Electronically Excited Energetic Salts: TKX-50 and MAD-X1

Abstract: Decomposition of energetic salts TKX-50 and MAD-X1 (dihydroxylammonium 5,5'-bistetrazole-1,1'-diolate and dihydroxylammonium 3,3'-dinitro-5,5'-bis-1,2,4-triazole-1,1'-diol, respectively), following electronic state excitation, is investigated both experimentally and theoretically. The NO and N2 molecules are observed as initial decomposition products from the two materials subsequent to UV excitation. Observed NO products are rotationally cold (<25 K) and vibrationally hot (>1500 K). The vibrational temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 64 publications
7
53
1
Order By: Relevance
“…Nevertheless, the activation barriers for real crystalline salts (like TKX-50 or MAD-X1) is expected to be high enough for a simple thermal occupation. This suggests the fairness of the previous results concerning conical intersections between S1 and S0 states [11].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Nevertheless, the activation barriers for real crystalline salts (like TKX-50 or MAD-X1) is expected to be high enough for a simple thermal occupation. This suggests the fairness of the previous results concerning conical intersections between S1 and S0 states [11].…”
Section: Discussionsupporting
confidence: 83%
“…To date, a two-step process initiated by a proton transfer from hydroxylammonium cations to 5,5'-bistetrazole-1,10-diolate is generally accepted [8][9][10][11][12][13][14][15]. Early molecular dynamics studies of thermal decomposition of TKX-50 revealed that the latter decays with release of molecular nitrogen or N2O with the activation energies of 188.7 and 302.1 kJ mol -1 , respectively [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Goddard et al, 18 developed a flexible classical force field for TKX-50, which reproduces the cell parameters, densities, lattice energy and mechanical properties derived from quantum mechanics (QM) and experiments. Bernstein et al, 19 explored the decomposition of the energetic salts TKX-50 and MAD-X1 (dihydroxylammonium 3,3'-dinitro-5,5'-bis-1,2,4-triazole-1,1'-diol) following electronic excitation via nanosecond energy resolved spectroscopy.…”
Section: Introductionmentioning
confidence: 99%